Analytical solution for electromagnetic diffraction on 2-D perfectly conducting scatterers of arbitrary shape. - Vesnik, M.V (IEEE Transactions on antennas and propagation)
A method is developed to receive a rigorous analytical solution of the external stationary two-dimensional (2-D) boundary value problem for the Helmholtz equation for perfectly conducting scatterers of an arbitrary shape. The rigorous expression for the scattered field is represented by the sum of integrals along piece-wise contours in a complex plane. In case of necessity a simple analytical asymptotic expression can be obtained